Pronomina Persona Bahasa Talang Mamak Kecamatan Rakit Kulim Kabupaten Indragiri Hulu - Binta Milyanniarti; Charlina Charlina; Mangatur Sinaga (STKIP PGRI Jombang, 2021)
AbstractThe aims of this research is to explain use of pronouns Talang Mamak Language, Rakit Kulims District, Indragiri Hulu Regency. This is a qualitative descriptive research. The methods of data collection were the observation process followed by the tapping technique, the skillful listening techhique involved, the listening technique free of charge, the recording technique, and technique of note taking. The technique of analyze the data starting by transcribe data after that data data checking and then classify, select, group, analyze, describe, and the last is concluded into a result of the research. On Talang Mamak Language, Rakit Kulim District, Indragiri Hulu Regency there a three design specifically singular first person pronouns aku, jaku, jawak. First person plural pronouns kami, kita. Second person plural pronouns kamu, kau. Third person singular pronoun liau and nyanya. Third person plural pronouns orang itu. The using of pronouns based on age and social status. Keyword: personal pronouns, form and use, Talang Mamak Language. AbstrakPenelitian ini bertujuan untuk mendeskripsikan penggunaan pronomina persona Bahasa Talang Mamak Kecamatan Rakit Kulim Kabupaten Indragiri Hulu. Jenis penelitian adalah penelitian deskriptif kualitatif. Metode pengumpulan data yaitu metode simak yang diikuti teknik sadap, teknik simak libat cakap, teknik simak bebas libat cakap, teknik rekam dan teknik catat. Teknik analisis data diawali dengan mentranskripkan data, setelah dilakukan transkip data lalu pengecekan data, setelah data dicek tahap selanjutnya ialah mengklasifikasi, menyeleksi, mengelompokkan, menganalisis, mendeskripsikan lalu terakhir disimpulkan menjadi laporan hasil penelitian. Pada Bahasa Talang Mamak Kecamatan Rakit Kulim Kabupaten Indragiri Hulu terdapat tiga bentuk pronomina persona yaitu kata ganti orang pertama tunggal yaitu aku, jaku, dan jawak, kata ganti orang pertama jamak yaitu kami dan kita. Kata ganti orang kedua tunggal yaitu kamu dan kau, kata ganti orang kedua jamak yaitu mika. Kata ganti orang ketiga tunggal yaitu liau dan nyanya, kata ganti orang ketiga jamak yaitu orang itu. Penggunaan pronomina tersebut berdasarkan usia, dan status sosial. Kata kunci: Pronomina persona, bentuk dan penggunaan, Bahasa Talang Mamak.